Effect of a Single Intrauterine Dose of Human Recombinant Galectin-1 Buffered on Pregnancy Rate in Inseminated Cows - Morani, Erika da Silva Carvalho; Penha, Helen Alves; Rey, Fernando Sebastián Baldi [UNESP]; Roncoletta, Marcelo (MDPI, 2022)
The objective was to evaluate the efficacy of a single dose of exogenous galectin-1 in improving the pregnancy rate in inseminated cows, comparing the pregnancy rate of the two groups (treatment and control Groups) into 107 contemporary groups (YG) established. An ultrasound exam determined the pregnancy rate performed 25 to 35 days after the fixed-time artificial insemination (FTAI) of breeding beef cows (n = 3469). The pregnancy rate of cows that received a single dose of eGAL-1 (200 ± 10 µg), with an intrauterine administration (n = 1901), was compared with the pregnancy rate of cows inseminated using a conventional AI protocol (n = 1568), both comparing into the same YG. YGs were created considering the grouping of cows belonging to the same farm, with the same nutritional score and management, inseminated by the same inseminator and semen batch, and using the same estrus synchronization protocol). The statistical method used calculated the probability of obtaining pregnancy within each group. The administration of a single dose of eGAL-1 can increase the probability of obtaining pregnancy in beef cows by up to 8.68% (p < 0.0001), suggesting that a single dose of eGAL-1 during the FTAI procedure was reasonable in the beef cattle AI routine and can improve the pregnancy rate considerably.
Keywords: Efficacy test; Fetal-maternal recognition; Mammals reproduction; Tolerana®